On the attenuation factor of time-dependent magnetic hyperfine interactions within the frame of the RPA model - Martínez, Jorge Alberto (1994)
Approximate analytical expressions for the attenuation factor of the time-dependent magnetic hyperfine interaction have been calculated assuming the hypothesis of the random phase approximation. The Fourier transforms of those expressions were also computed. Different relaxation regimes were considered rangingλ/ωL over 1/4, 1/2, 3/4 and 1/1 ratios.